2019
DOI: 10.1021/acsami.9b07021
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanoheterostructure of Tungsten Disulfide Nanoflowers Doped with Zinc Oxide Hollow Spheres: Benzene Gas Sensing Properties and First-Principles Study

Abstract: This paper reports an original fabrication of a benzene gas sensor based on tungsten disulfide nanoflowers (WS2 NFs)/zinc oxide hollow spheres (ZnO HMDs) hierarchical nanoheterostructure. The ZnO/WS2 hierarchical composite was characterized for the inspection of its nanostructure, elementary composition, and surface morphology. The benzene-sensing properties of the ZnO/WS2 nanofilm sensor were exactly investigated. The results illustrate that the ZnO/WS2 sensor exhibits a remarkable sensing performance toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 60 publications
0
33
0
Order By: Relevance
“…where, c is the electron affinity of the ZnO (3.2 eV), 4 off is the offset in the estimated work function of the conducting probe found during calibration ($32 meV) on the Au lm (4 M ¼ 5.1 eV) and E F is the Fermi level related to the conduction band minimum. 28 Using eqn (11), the estimated surface band bending (SBB) of ZnO nanowires before NO 2 exposure was 1.92 eV which was increased upto 1.96 eV during NO 2 exposure. Interestingly, the surface band bending for ZnO@In 2 O 3 heterojunction nanowires was increased up to 2.04 eV compared to pristine ZnO nanowires.…”
Section: Evaluation Of the No 2 Sensing Performance Of Zno@in 2 O 3 Heterojunction Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…where, c is the electron affinity of the ZnO (3.2 eV), 4 off is the offset in the estimated work function of the conducting probe found during calibration ($32 meV) on the Au lm (4 M ¼ 5.1 eV) and E F is the Fermi level related to the conduction band minimum. 28 Using eqn (11), the estimated surface band bending (SBB) of ZnO nanowires before NO 2 exposure was 1.92 eV which was increased upto 1.96 eV during NO 2 exposure. Interestingly, the surface band bending for ZnO@In 2 O 3 heterojunction nanowires was increased up to 2.04 eV compared to pristine ZnO nanowires.…”
Section: Evaluation Of the No 2 Sensing Performance Of Zno@in 2 O 3 Heterojunction Nanowiresmentioning
confidence: 99%
“…ZnO having a hexagonal crystal plane arrangement with a wurtzite structure along with a huge exciton binding energy of 60 meV is considered to be an ideal semiconductor for NO 2 gas sensors. [11][12][13] However, though ZnO is being used in conventional MOS gas sensors, the issues associated with poor selectivity, high operating temperature and reliability hinder its practical applications. Similarly, n-type In 2 O 3 (rhombohedral structure) has also gained signicant attention towards NO 2 detection owing to its unique characteristics such as an extensive energy gap (2.5-3.75 eV), high electrical conductivity etc.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [20a] reported that trace detection of ethanol was achieved by adjusting the surface absorption, electron transport path and electron transfer efficiency of SnO 2 /ZnO fiber grade structure. Zhang et al [80] reported that the electron depletion layer was formed on the side of ZnO and the hole-depletion layer was formed on the side of WS 2 due to the Fermi level difference between ZnO and WS 2 , leading to an increase of initial resistance. The materials structure is also an important factor affecting gas sensitive properties.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Operation at RT is the biggest challenge for sensors based on metal oxide semiconductors, and this had led to the development of ways to overcome this inconvenience. These approaches include doping [ 92 , 93 , 94 ], obtaining heterojunctions from p and n-type semiconductors [ 95 , 96 ], developing special microstructures [ 97 , 98 ], and inducing oxygen vacancies or the use of composite materials [ 86 , 99 , 100 ]. Among the most used and known methods of synthesis of doped materials are chemical vapor deposition, the hydrothermal method, the sol-gel method, and thermal annealing [ 101 ].…”
Section: Sensitive Materials Used In Gas Detectionmentioning
confidence: 99%